Bridging the Cultural Gap: Protest and Social Movements (from Mai 68 to 15-M and beyond) (KULT_online, 2015)
This volume edited by Britta Baumgarten, Priska Daphi and Peter Ullrich adds the crucial element of culture to the puzzle of contemporary social movement research. By complementing and going beyond the state of the art in social movement research, it offers critical, interdisciplinary, and translocal perspectives in four sections to tackle the concept of culture for social movement research. From the protests of 15-M in Madrid and to Mai 68, this volume updates the idea of social movements as new historical subjects and convincingly bridges the cultural gap in social movement research.